EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN TRAINER KIT INSTALASI MOTOR LISTRIK - Hasana, Frida; Novriyanti; Aqthobirrobbany, Aqil; Triantini , Dewi (Jurnal Muara Pendidikan, 2025)
This research aim to determine differences in student learning outcomes between those who use a problem-based learning model  assisted  by trainer  kit  with those who  do  not  use it. The learning outcomes are seen from the cognitive, affective, and psychomotor aspects of students. Beside that, this research also to find out how effective the use of the trainer kit in terms of cognitive aspects. This study was a quasi-type experiment with research design Non-Equivalent Control Group Design. Learning outcomes from the experimental class and the control class were then analyzed using the T test and Gain test with a significance value of 0.05.After analysed, the T test shows that the cognitive aspects of the significance value (0.002 < 0.05), significance value of affective aspects (0.004 < 0.05), and significance of psychomotor aspects (0.00 < 0.05). While the average Gain test results show that the experimental class learning outcomes are higher than the control class (0.566> 0.280). The data concludes that the use of a problem-based learning model assisted by trainer kits is more effective in improving student learning outcomes.